Cooperation between Candidatus Competibacter and Candidatus Accumulibacter clade I, in denitrification and phosphate removal processes. (1st September 2017) - Rubio-Rincón, F.J.; Lopez-Vazquez, C.M.; Welles, L.; van Loosdrecht, M.C.M.; Brdjanovic, D.
Abstract: Although simultaneous P-removal and nitrate reduction has been observed in laboratory studies as well as full-scale plants, there are contradictory reports on the ability of PAO I to efficiently use nitrate as electron acceptor. Such discrepancy could be due to other microbial groups performing partial denitrification from nitrate to nitrite. The denitrification capacities of two different cultures, a highly enriched PAO I and a PAO I-GAO cultures were assessed through batch activity tests conducted before and after acclimatization to nitrate. Negligible anoxic phosphate uptake coupled with a reduction of nitrate was observed in the highly enriched PAO I culture. On the opposite, the PAO I-GAO culture showed a higher anoxic phosphate uptake activity. Both cultures exhibited good anoxic phosphate uptake activity with nitrite (8.7 ± 0.3 and 9.6 ± 1.8 mgPO4 -P/gVSS.h in the PAO I and PAO I-GAO cultures, respectively). These findings suggest that other microbial populations, such as GAOs, were responsible to reduce nitrate to nitrite in this EBPR system, and that PAO I used the nitrite generated for anoxic phosphate uptake. Moreover, the simultaneous denitrification and phosphate removal process using nitrite as electron acceptor may be a more sustainable process as can: i) reduce the carbon consumption, ii) reduce oxygen demand of WWTP, and iii) due to a lower growth yield contribute to a lower sludge production. Graphical abstract: Highlights: A PAO I culture did not perform a significant anoxic P-uptake using nitrate. A PAO I-GAO culture showed a higher anoxic P-removal activity on nitrate. GAO contributed to the reduction of nitrate to nitrite thereby supporting the anoxic activity of PAO.